Analysis Of Marketing Patterns of Lumi-Lumi (Harpodon sp) in Ujong Baroh PPI, West Aceh - Sari, Yelsi Afita; Amarullah, Teuku; Zuriat, Zuriat; Rizal, Muhammad (Universitas Teuku Umar, 2024)
PPI Ujong Baroh in West Aceh Regency is one of the areas with high Bombay Duck Fish production. Bombay Duck Fish is a highly perishable food that must quickly reach the end consumer to keep it good. This study aims to determine the marketing pattern of Bombay Duck Fish and determine the most efficient marketing channel. This research was conducted in January - February 2024 at PPI Ujong Baroh. The research data were analyzed using marketing margin analysis, farmer share, and marketing efficiency. The results of this study indicate that there are three patterns of fish marketing, namely first fishermen - toke bangku - retailers - consumers, second fishermen - toke bangku – muge (traveling salesmen) - consumers and third fishermen - toke bangku - consumers. The marketing margin obtained in channel pattern I is Rp 10,317, in channel pattern II Rp 13,333, and in channel pattern III Rp 5000. The margin of channel III marketing pattern is the most efficient marketing. While farmer share in channel pattern I amounted to 31 %, channel pattern II amounted to 28 %, and channel pattern III amounted to 45%, the most efficient value in marketing pattern III. Furthermore, efficiency in channel pattern I amounted to 10 %, in channel pattern II amounted to 7 %, and in channel pattern III amounted to 4 %. The most efficient marketing channel is channel pattern III with a margin value of Rp 6,700, a farmer shere value of 45 %, and an efficiency of 4 %. The fewer the number of institutions involved in the marketing channel and the small margin value, the more efficient the channel pattern is in marketing Bombay Duck Fish.